SCADA Implementation on Solar Panel Electricity Consumption Monitoring and Regulation System - Sawidin, Sukandar; Tracy M. Kereh; Donald B. Noya; Yoice R. Putung; Yudita F. Rotti (Engineering And Technology Journal, 2024)
In an effort to motivate students and understand application of SCADA to the Solar Panel system which is one source potential non - fossil energy to be used as solution to meeting sustainable energy needs.​ Where in its operation , efficiency and reliability Solar Panel system is still a major problemthat must be overcome . Utilization of Supervisory Control and Data Acquisition (SCADA) in management Solar Panel Systems (PLTS) have become significant solution​ to improve loading efficiency . The purpose of this research is to create a prototypes solar panel practicum as a learning media to motivate student in understanding how solar panels work and can apply the process of monitoring and regulating solar panel system with SCADA in real-time. The equipment used​ includes Solar Panels, Solar Charger Controller (SCC), Inverter, Battery , PLC Omron CP1E-NA20DR-A and CP1W AD041, ACS712 Current Sensor , ZMPT101B Voltage Sensor, DHT22 Temperature and Humidity Sensor and Light Sensor (LDR) as well as CX- Programmer software Ver. 9.5 and CX -Supervidor Ver.4.0. The method used is Research and Development method as the basic for design and manufacture of solar panel practicum tools and the application of SCADA to the monitoring system and electricity usage of solar panels . From the results of tests conducted with the application of SCADA on solar panels can monitor Voltage , Current , Power, Temperature , Light and load usage regulator electric solar panels based on electrical energy consumption, as well as the condition of electrical equipment connected to the solar panel system with an average error values : Voltage 0.084%, Current 0.155%, Power 0.107% and Temperature 45 0C and Light 658.7 Lux.